2022
DOI: 10.1080/19490976.2022.2038855
|View full text |Cite
|
Sign up to set email alerts
|

Timing of antimicrobial prophylaxis for cesarean section is critical for gut microbiome development in term born infants

Abstract: Animal models imply that the perinatal exposure to antibiotics has a substantial impact on microbiome establishment of the offspring. We aimed to evaluate the effect of timing of antimicrobial prophylaxis for cesarean section before versus after cord clamping on gut microbiome composition of term born infants. We performed an exploratory, single center randomized controlled clinical trial. We included forty pregnant women with elective cesarean section at term. The intervention group received single dose intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 74 publications
0
12
0
Order By: Relevance
“…In other situations, cefuroxime 1500 mg dose is recommended if MIC 90 of ≥ 8 µg/g are desired for at least 95% of women at 2 h post dose; if the CS is delayed > 2 h post cefuroxime administration of 1500 mg in lean, obese, or morbidly obese pregnant women, a second dose might be required to maintain cefuroxime concentrations ≥ 8 µg/g or µg/mL (Tables S5 and S6). Balancing the benefit vs. the maternal/foetal safety should be considered [64].…”
Section: Cefuroximementioning
confidence: 99%
“…In other situations, cefuroxime 1500 mg dose is recommended if MIC 90 of ≥ 8 µg/g are desired for at least 95% of women at 2 h post dose; if the CS is delayed > 2 h post cefuroxime administration of 1500 mg in lean, obese, or morbidly obese pregnant women, a second dose might be required to maintain cefuroxime concentrations ≥ 8 µg/g or µg/mL (Tables S5 and S6). Balancing the benefit vs. the maternal/foetal safety should be considered [64].…”
Section: Cefuroximementioning
confidence: 99%
“…As large trials and meta-analyses revealed a lower risk for complications when antibiotics are given before skin incision 11 38 39 , guidelines changed and now recommend the administration of antibiotics 30 to 120 minutes before skin incision 40 41 42 . This, however, leads to an intrauterine exposure to antibiotics of all infants born by CS and there is evidence that even a single dose of antibiotics has an impact on early neonatal gut microbiome development 43 . A recent prospective multicenter study from Switzerland did not find an increased risk for infections in mothers who received the antibiotic after cord clamping.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been shown that the way an infant is born and the amount of antibiotics they are exposed to during the perinatal period can affect the development of the gut microbiome establishment and have long-term impacts on their health, such as increasing the risk of asthma, inflammation, and obesity 117 , 118 .…”
Section: Factors Affecting Antibiotic Resistance In Infantsmentioning
confidence: 99%